Active breaks and improvemnt of learnings in preschool: a proposal of intervention - Pastor-Vicedo, JC.; Martínez-Martínez, J.; Jaén Tévar, Y.; Prieto-Ayuso, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The objective of this work is the study of the relationship between active breaks and academic performance in children preschool education, improving the curricular contents, through physical education games. The sample was formed by 50 participants, divided into a control group (n = 25) and an experimental group (n = 25). For the data collection, two evaluations were conducted, one before the programme (pre) and the other one after the programme (post). For the data analysis the t-Student test was used. The results obtained reflected the importance of physical activity in academic performance, as well as the transversal benefits it brings to health.